Investigation of Natural Compounds for Therapeutic Potential in Streptozotocin-induced Diabetic Neuroinflammation and Neuropathic Pain - Faheem, Muhammad; Khan, Arif-ullah; Shah, Fawad Ali; Li, Shupeng (Frontiers in pharmacology, 2022)
Diabetic neuropathy (DN) is a serious microvascular complication of diabetes mellitus (DM) that impacts the nervous system. Several risk factors are involved in the progression and maintenance of DN-associated pain, such as higher expression of various inflammatory mediators, e.g., tumor necrotic factor-alpha (TNF-α), nuclear factor-kappa B (NF-κB), and cyclo-oxygenase-2 (COX-2). The present research explores the neuroprotective potential of natural isolates, including berbamine, bergapten, and carveol, on the DM-induced neuroinflammation and neurodegeneration that cause neuropathic pain. The study utilized computerized techniques, including computational analysis (a docking assay and a molecular dynamic simulation) before moving to in vivo protocols. Diabetic neuropathy was induced by intraperitonial injection (IP) of streptozotocin (65 mg/kg), and the animal subjects (rats) were kept for 4 weeks for the development of DN. Once diabetic neuropathy was confirmed, the subjects were treated with berbamine, bergapten, and carveol until the sixth week (i.e., 2 weeks of treatment). At the sixth week, the rats were sacrificed, and the sciatic nerve and spinal cord of each was collected for further molecular investigation. Docking and a molecular dynamic simulation (MDS) delivered the information that the natural compounds (berbamine, bergapten, and carveol) were interacting with the selected target protein (i.e., mitogen-activated protein kinase). After IP, it was found that berbamine, bergapten, and carveol had ameliorated mechanical allodynia and thermal hyperalgesia by the 28th day of the study (2 weeks after treatment) without affecting blood glucose levels. Berbamine, bergapten, and carveol markedly elevated the levels of glutathione (GSH) and glutathione s-transferase (GST), in both the sciatic nerve and spinal cord, and also reduced lipid peroxidase (LPO) and nitric oxide (NO). The abovementioned natural isolates reduced pathologic alterations provoked through DN, a finding confirmed through histopathological assays (hematoxylin and eosin staining and immuno-histochemical analysis). Treatment down regulated higher expressions of the inflammatory mediatorcyclooxygenase-2 (COX-2), tumor necrosis factor-α (TNF-α), and nuclear factor kappa B (NF-κB), as confirmed by ELISA and polymerase chain reaction (PCR). The outcomes of berbamine, bergapten, and carveol are compared with those of pregabalin as a positive control group. Compared to pregabalin, treatment with the aforementioned three natural compounds improved nociception and reduced hyperalgesic effects, and consequently reduced pain perception and inflammation. Our results suggest the mechanism for the neuro-protective impact of berbamine, bergapten, and carveol might possibly be arbitrated via COX-2, TNF-α, and NF-κB, and regulated by mitogen-activated protein kinase, ultimately ameliorating STZ-provoked, DM-induced neuroinflammation and neurodegeneration, and associated neuropathic pain.